2018
DOI: 10.1080/00015385.2018.1475093
|View full text |Cite
|
Sign up to set email alerts
|

Elevated oxidative DNA damage in patients with coronary artery disease and its association with oxidative stress biomarkers

Abstract: There was significant increase in oxidative DNA damage and oxidative stress in CAD patients compared to levels in healthy controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Sirtuin 1 (SIRT1) is an NAD + -dependent protein deacetylase that is involved in cell differentiation, aging, apoptosis, physiological rhythms, metabolic regulation, oxidative stress and numerous other important biological processes. Furthermore, it has an important biological role in transcriptional regulation (7). Studies have demonstrated that SIRT1 is required for the maintenance of normal cognitive function and synaptic plasticity regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Sirtuin 1 (SIRT1) is an NAD + -dependent protein deacetylase that is involved in cell differentiation, aging, apoptosis, physiological rhythms, metabolic regulation, oxidative stress and numerous other important biological processes. Furthermore, it has an important biological role in transcriptional regulation (7). Studies have demonstrated that SIRT1 is required for the maintenance of normal cognitive function and synaptic plasticity regulation.…”
Section: Introductionmentioning
confidence: 99%
“…It should be stressed that patients with CVD are characterized with increased oxidative DNA damage and decreased antioxidative status comparing to healthy subjects, which in turn may contribute to oxidative stress-related neuropsychiatric pathologies 47 . Current results indicate that MDD prior to surgery is strongly and independently associated with postoperative delirium.…”
Section: Discussionmentioning
confidence: 99%
“…2 Apart from the traditional risk factors, oxidative stress is also a strong contender in the development of CAD. 3 Oxidative stress hampers the activity of cells and releases reactive oxygen species (ROS). This in turn results in the secretion of cyclophilin A (CypA), a proinflammatory mediator from vascular smooth muscle cells (VSMCs) and macrophages.…”
Section: Introductionmentioning
confidence: 99%